Buenellus chilhoweensis n. sp. from the Murray Shale (lower Cambrian Chilhowee Group) of Tennessee, the oldest known trilobite from the Iapetan margin of Laurentia. (26th March 2018) - Webster, Mark; Hageman, Steven J.
Abstract: The Ediacaran to lower Cambrian Chilhowee Group of the southern and central Appalachians records the rift-to-drift transition of the newly formed Iapetan margin of Laurentia. Body fossils are rare within the Chilhowee Group, and correlations are based almost exclusively on lithological similarities. A critical review of previous work highlights the relatively weak biostratigraphic and radiometric age constraints on the various units within the succession. Herein, we document a newly discovered fossil-bearing locality within the Murray Shale (upper Chilhowee Group) on Chilhowee Mountain, eastern Tennessee, and formally describe a nevadioid trilobite, Buenellus chilhoweensis n. sp., from that site. This trilobite indicates that the Murray Shale is of Montezuman age (provisional Cambrian Stage 3), which is older than the Dyeran (provisional late Stage 3 to early Stage 4) age suggested by the historical (mis)identification of " Olenellus sp." from within the unit as reported by workers more than a century ago. Buenellus chilhoweensis n. sp. represents only the second known species of Buenellus, and demonstrates that the genus occupied both the Innuitian and Iapetan margins of Laurentia during the Montezuman. It is the oldest known trilobite from the Iapetan margin, and proves that the hitherto apparent absence of trilobites from that margin during the Montezuman was an artifact of inadequate sampling rather than a paleobiogeographic curiosity. The species offers a valuable biostratigraphic calibration point within a rock succession that has otherwise proven recalcitrant to refined dating. UUID:http://zoobank.org/30af790b-e7b1-44c3-b1d5-55cdf579bde2